2019
DOI: 10.3390/ijms20133172
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Relevant Alternative Carbon Sources Modulate Biofilm Formation, Cell Wall Architecture, and the Stress and Antifungal Resistance of Candida glabrata

Abstract: Flexibility in carbon metabolism is pivotal for the survival and propagation of many human fungal pathogens within host niches. Indeed, flexible carbon assimilation enhances pathogenicity and affects the immunogenicity of Candida albicans. Over the last decade, Candida glabrata has emerged as one of the most common and problematic causes of invasive candidiasis. Despite this, the links between carbon metabolism, fitness, and pathogenicity in C. glabrata are largely unexplored. Therefore, this study has investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…These cell wall-remodeled C. albicans cells become resistant to amphotericin B (AMB) and caspofungin (Ene et al, 2012). Similar results were demonstrated for C. glabrata strains that grown under an alternative carbon microenvironment showed altered cell wall architecture with a lower content of chitin and β-glucan, and with an increased outer mannan layer (Chew et al, 2019). These C. glabrata cells were also resistant to AMB when grown in lactate or oleate (Chew et al, 2019).…”
Section: Fungal Cell Wall Modifications and Antifungal Resistancesupporting
confidence: 77%
“…These cell wall-remodeled C. albicans cells become resistant to amphotericin B (AMB) and caspofungin (Ene et al, 2012). Similar results were demonstrated for C. glabrata strains that grown under an alternative carbon microenvironment showed altered cell wall architecture with a lower content of chitin and β-glucan, and with an increased outer mannan layer (Chew et al, 2019). These C. glabrata cells were also resistant to AMB when grown in lactate or oleate (Chew et al, 2019).…”
Section: Fungal Cell Wall Modifications and Antifungal Resistancesupporting
confidence: 77%
“…Gluconeogenic genes are also induced in vivo (21,57), and these transcriptional changes are often advantageous for microbial pathogens. Stress resistance induced in the presence of alternative carbon sources has been observed in other Candida species, including C. glabrata and the emerging pathogen C. auris (58,59), and numerous examples of beneficial effects of utilization of alternative carbon sources have been seen in bacterial pathogens. For example, Staphylococcus aureus, a facultative intracellular pathogen, alters its central carbon metabolism to promote its survival in the phagosome (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the capability of carbon assimilation has been reduced significantly in comparison to S. cerevisiae . In fact, C. glabrata is unable to utilize many carbon sources such as galactose, maltose, lactose, sucrose and raffinose and mainly rely on glucose and trehalose [ 36 ], it has been shown to be able to utilize certain alternative carbon sources such as carboxylic acids, fatty acids and alcohols [ 13 ]. Furthermore, adaptation to these alternative carbon sources also induced physiological changes associated with pathogenicity of C. glabrata .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, addition of acetic acid to glucose-grown C. glabrata renders the cells to be more sensitive to fluconazole treatment, and these cells are also more susceptible to phagocytosis killing by macrophages [ 12 ]. Previously, we have demonstrated that alternative carbon sources also induce physiological changes related to the pathogenicity of C. glabrata [ 13 ]. These include changes in planktonic and biofilm growth, cell wall architecture, oxidative stress resistance and antifungal susceptibility.…”
Section: Introductionmentioning
confidence: 99%